(untitled) (Sains Humanika, 2025)
Students with visual impairment (SVI) are among the minority groups in society who greatly require specialized assistive technologies to receive information from their surroundings. Therefore, the approach often used in schools is to develop teaching aids with specific features that can help them access information. Therefore, this study focuses on obtaining expert validation for the development of a specific instrument that addresses the needs of SVI in the creation of ABM—particularly in the use of 3D printing (3DP) technology as a component of tactile technology. In this study, the research approach used is Design and Development Research (DDR). The expert validation represents the initial phase of the second stage (design and development) to obtain consensus from experts in establishing content items that can measure the needs of these students. A total of three (3) experts were involved in this study. The developed instrument is a questionnaire consisting of four (4) main sections: language, curriculum, pedagogy, and design (design, color coding, audio, Braille writing). The content validity analysis was conducted using the Content Validity Index (CVI) method. The findings indicate that the developed instrument has a satisfactory validity value with a CVI score of 1.00—demonstrating that the items developed are accurate in evaluating teaching aids specifically for SVI. Therefore, the developed instrument is deemed suitable for assessing teaching aids that utilize tactile and audio technology specifically for SVI use.